Synthesis , identification and evaluation of antibacterial activity for some new heterocyclic derivatives from 4-methoxy-2-nitroaniline - Sabah Matrood Mezaal; Shaimaa Adnan (Al-Qadisiyah Journal of Pure Science, 2021)
This research involved synthesis. novel  heterocyclic derivatives (quinazoline and thiazinone)  derivatives , this compounds prepared from starting react (4-methoxy-2-nitroaniline) with 2,4-dimethoxyacetophenone  to gate azo derivative (A) , (A) interact with aromatic amine derivatives to produce imine compounds (B1-B2), imine derivatives  interact with (anthranilic acid , 2-mercaptobenzoic) to get heterocyclic derivatives quinazoline (C1-C2) and thiazinone (D1-D2 ) . All these compound characterized by13 C-NMR , FT-IR , 1HMNR . Then that,we studies the,biological,properties for,all heterocyclic  derivatives,to,ward.two different kindof bacteria.